Motivational and cognitive benefits of training in immersive virtual reality based on multiple assessments - Makransky, Guido; Borre‐Gude, Stefan; Mayer, Richard E. (Journal of computer assisted learning, 2019)
The main objective of this study was to examine the effectiveness of immersive virtual reality (VR) as a medium for delivering laboratory safety training. We specifically compare an immersive VR simulation, a desktop VR simulation, and a conventional safety manual. The sample included 105 first year undergraduate engineering students (56 females).  We include five types of learning outcomes including post‐test enjoyment ratings; pre‐ to post‐test changes in intrinsic motivation and self‐efficacy; a post‐test multiple choice retention test; and two behavioral transfer tests. Results indicated that the groups did not differ on the immediate retention test, suggesting that all three media were equivalent in conveying the basic knowledge. However, significant differences were observed favoring the immersive VR group compared to the text group on the two transfer tests involving the solving problems in a physical lab setting (d = 0.54, d = 0.57), as well as enjoyment (d = 1.44) and increases in intrinsic motivation (d = 0.69) and self‐efficacy (d = 0.60). The desktop VR group scored significantly higher than the text group on one transfer test (d = 0.63) but not the other (d= 0.11), as well as enjoyment (d =1.11) and intrinsic motivation (d =0.83). Lay Description What is currently known about the subject matter Virtual reality (VR) is increasingly being used to deliver learning and training material. One field where the affordances of VR are particularly relevant is in safety training. VR provides the opportunity for trainees to safely act out realistic scenarios where making the right decisions is pivotal and training in real life would otherwise be impractical or impossible. Most studies that investigate the effectiveness of learning with VR do not include behavioural transfer tests. What this paper adds to this research This study used a broad array of assessment methods to evaluate the effectiveness of safety training delivered with three different instructional media: an immersive VR simulation, a desktop VR simulation, and a conventional text‐based safety manual. There were no differences between conventional and VR training on a retention test. The immersive VR group significantly outperformed the conventional group on two behavioural transfer tests, perceived enjoyment, and increase in intrinsic motivation and self‐efficacy. The desktop VR group scored significantly higher than the conventional group on one behavioural transfer test, perceived enjoyment, and increase in intrinsic motivation. The results suggest that behavioural measures of transfer in realistic settings may be necessary to accurately assess the instructional value of VR learning environments.